2014
DOI: 10.1007/s13632-014-0172-2
|View full text |Cite
|
Sign up to set email alerts
|

Processing and Deformation Behavior of Bulk Cu–Nb Nanolaminates

Abstract: Metallic nanolaminates, composed of alternating layers of two dissimilar metals, have attracted significant attention due to both their high strengths and their potential for excellent microstructural stability. While nanolaminates have traditionally been available only in thin-film form, advances in the severe plastic deformation process of accumulative roll bonding (ARB) have enabled the production of 4-mm-thick sheets of copper-niobium nanolaminates containing over 200,000 individual layers (a nominal layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 22 publications
2
16
0
Order By: Relevance
“…As a promising alternative, researchers have applied SPD to make layered composites in bulk via a technique called accumulative roll bonding (ARB) [20][21][22]. The ARB process uses an iterative sequence of cleaning, stacking, roll bonding, and cutting to create and refine a lamellar microstructure [23]. This technique has been applied to several different bimetal systems [21,22,[24][25][26][27].…”
Section: Stability Of Metallic Materials Under Extreme Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a promising alternative, researchers have applied SPD to make layered composites in bulk via a technique called accumulative roll bonding (ARB) [20][21][22]. The ARB process uses an iterative sequence of cleaning, stacking, roll bonding, and cutting to create and refine a lamellar microstructure [23]. This technique has been applied to several different bimetal systems [21,22,[24][25][26][27].…”
Section: Stability Of Metallic Materials Under Extreme Strainsmentioning
confidence: 99%
“…The material can be further processed down to individual layer thicknesses < 10 nm. [23] The ARB process imposes rolling deformation. Rolling can stabilize certain crystallographic orientations, known as ideal rolling components.…”
Section: Stable Orientations and Stable Orientation Relationshipsmentioning
confidence: 99%
“…These include deposited {001}, {110}, and {111} textures. Severe plastic deformation (SPD) of two-phase composites is another way of forming nanomaterials 37 . These tend to produce textures where the interface planes correspond to {112} planes and the two in-plane directions of the NC Cu phase, the <111> and <110> directions, are highly aligned 38 .…”
Section: Materials and Nanostructurementioning
confidence: 99%
“…Bimetallic‐multilayered composite sheets that consist of two distinct, alternatively stacked metals have the potential to satisfy these requirements, especially if they comprise low‐density metals, such as Mg. Prior works, not involving Mg, have shown that bimetallic‐layered sheets with very fine individual layer thicknesses, ranging from as low as submicron to nanometer dimensions, can exhibit a plethora of outstanding properties simultaneously . This is due to a change in deformation mechanisms as the region between bimetal interfaces become more constricted and plasticity becomes more limited and difficult to activate .…”
Section: Introductionmentioning
confidence: 99%
“…This is due to a change in deformation mechanisms as the region between bimetal interfaces become more constricted and plasticity becomes more limited and difficult to activate . Cu/Nb nanolaminates, for instance, have demonstrated the outstanding thermal stability, strength, shock resistance, radiation resistance, and even ductility . Attaining such fine layers involves application of large plastic deformation during the metal‐forming process.…”
Section: Introductionmentioning
confidence: 99%